Political and Nationalism of GP Ansor in Facing The Perssecution of Kirab Satu Negeri in The Meranti Islands - Imam Ghozali; Junaidi Junaidi (IAIN Ponorogo, 2020)
Abstract: This study is to determine the implementation, implication, and process of resolving the politics of nationalism in the Kirab Satu Negeri GP Ansor activities in the Meranti Islands. This activity experienced persecution from HTI, FPI, youth organizations, and the Malay Customary Institution (LAM) of the Meranti Islands Regency. The movement of negative opinions by these mass organizations has worsened the image of GP Ansor in the Meranti community. This research uses a qualitative descriptive-analytic approach. The data collection method in this study combines the Library Method and Field Research. As a result of the research, GP Ansor applies the politics of religious nationalism in carrying out the Kirab Satu Negeri. Indeed, radicalism groups and youth organizations build negative opinions of political and religious issues the affect the solidity of members of the GP Ansor, divided into two, namely following the line of command of the GP Ansor board and some rejecting it firmly. The GP Ansor militant committee consistently moves to resolve the persecution with religious nationalism politics, namely: first to open a dialogue with mass organizations that reject the KSN program; second, to conduct friendship wit LAM elders with the connectivity approach of the similarity between the NU tradition and the rituals of the Malay community; the third structural approach to the local Government, DPRD and Kapolres regarding the KSN mission to arouse the spirit of nationality; fourth, inviting all members of the GP Ansor, officials to do istighosah so that Indonesia will not be able to be divided by radical groups.الملخص: تهدف هذه الدراسة إلى تحديد التنفيذ والتضمين وعملية حل المشكلة حول سياسات القومية في أنشطة كيراب ساتو نيجيري حركة الشباب أنصار (GP Ansor) في جزر ميرانتي. تعرض هذا النشاط للاضطهاد من قبل حزب التحرير الإندو نسي( HTI) و جبهة الدفاع الإسلامي( FPI) ومنظمات الشباب ومؤسسة العرفية المالايووية(LAM) في منطقة جزر ميرانتي . أدت توجيه الآراء السلبية من قبل هذه المنظمات الجماهيرية إلى تدهور صورة حركة الشباب أنصار في نظر مجتمع ميرانتي Meranti. يستخدم هذا البحث المنهج الوصفي التحليلي. بينما طريقة جمع البيانات في هذه الدراسة تجمع بين أسلوب المكتبة والبحث الميداني. و نتيجة البحث ، يطبق حركة الشباب أنصار سياسة القومية الدينية في تنفيذ كيراب ساتو نيجيري( KSN/Kirab Satu Negeri). وبالفعل ، فإن الجماعات الراديكالية والمنظمات الشبابية تبني آراء سلبية حول القضايا السياسية والدينية التي تؤثر على صلابة أعضاء GP Ansor و إنقسامهم إلى قسمين. منهم من اتبع خط القيادة لإدارة GP Ansor و الأخر صارم على رفض ذلك. مازال المجلس الإداري المتشدد في GP Ansor يتحرك لحل هذا الاضطهاد بسياسات القومية الدينية ، أي: أولا فتح باب الحوار مع المنظمات الجماهيرية التي ترفض برنامج (KSN) ؛ ثانيًا ، إقامة التواصل والصداقة مع شيوخ (LAM) من خلال نهج الترابط للتشابه بين تقاليد نهضة العلماء (NU) وطقوس مجتمع الملايو. ثالثا، القيام بالتقرب الهيكلي إلى حكومة المحلية و مجلس الشورى المنطقي (DPRD) و رئيس الأمن المنطقي (Kapolres) فيما يتعلق بمهمة (KSN) لإثارة روح الجنسية ؛ رابعًا ، الدعوة لجميع أعضاء (GP Ansor) ، والمسؤولين للقيام بالإستغاثة حتى تتجنب الدولة الإندونيسية من الانقسام بسبب عمل الجماعات المتطرفة.Abstrak: Penelitian ini untuk mengetahui implementasi, implikasi dan proses penyelesaian politik nasionalisme pada kegiatan Kirab Satu Negeri (KSN) GP Ansor Kepulauan Meranti. Kegiatan ini mengalami persekusi dari HTI, FPI, Ormas Kepemudaan dan Lembaga Adat Melayu (LAM) Kabupaten Kepulauan Meranti. Penggiringan opini negatif oleh kelompok Ormas-ormas tersebut telah memperburuk citra GP Ansor di masyarakat Meranti. Penelitian ini menggunakan pendekatan kualitataif deskriptif analistis. Sedangkan metode pengumpulan data dalam penelitian ini menggabungkan antara metode kepustakaan dan penelitian lapangan. Hasil penelitian menyimpulkan bahwa GP Ansor menerapkan politik nasionalisme religius dalam menjalankan Kirab Satu Negeri. Kelompok radikalisme dan Ormas kepemudaan membangun opini negatif tentang isu-isu politik dan agama yang mempengaruhi solidaritas anggota GP Ansor sehingga terpecah menjadi dua, yaitu sebagian mengikuti garis komando pengurus GP Ansor dan sebagain menolak secara tegas. Pengurus militan GP Ansor konsisten terus bergerak menyelesaikan persekusi dengan politik nasionalisme religius, yaitu pertama membuka dialog dengan Ormas-ormas yang menolak acara KSN; kedua melakukan silaturahi dengan sesepuh LAM dengan pendekatan konektivitas kesamaan antara tradisi NU melalui ritual masyarakat Melayu; ketiga melakukan pendekatan struktural kepada Pemuda, DPRD dan Kapolres tentang misi KSN untuk membangkitkan semangat kebangsaan; keempat mengajak seluruh anggota GP Ansor, para pejabat untuk istighasah agar negara Indonesia terhindar dari perpecahan akibat dari kelompok-kelompok radikalisme.